Sn1−xSe thin films with low thermal conductivity: role of stoichiometric deviation in thermal transport. Issue 37 (7th September 2018) - Jeong, Giuk; Jaung, Yoon Hwan; Kim, Jekyung; Song, Jae Yong; Shin, Byungha
Abstract : Tin selenide (Sn1− x Se) polycrystalline thin films were prepared by thermal co-evaporation, and the thermoelectric properties of the Sn1− x Se thin films were investigated. Abstract : Tin selenide (Sn1− x Se) polycrystalline thin films were prepared by thermal co-evaporation, and the thermoelectric properties of the Sn1− x Se thin films were investigated. We found that a stoichiometric SnSe thin film has a lower thermal conductivity than the bulk form of SnSe reported in the literature. As the composition deviated from the stoichiometry ( i.e., x > 0), interesting changes in thermal conductivity were observed: a general trend of increasing thermal conductivity with increasing x except that the lowest thermal conductivity was observed when x ∼ 0.3. Two factors are identified to influence the dependence of thermal conductivity on the composition: a portion of the SnSe2 phase that has a higher thermal conductivity than SnSe and the density of the SnSe/SnSe2 interface, which is expected to be effective in phonon scattering because of a higher Kapitza resistance. An interplay between these two factors leads to the minimum thermal conductivity at x ∼ 0.3. Our study provides new strategies that can potentially lead to the improved thermoelectric performance of SnSe: use of thin films and careful control of the composition.